HUBUNGAN ANTARA FAKTOR SOSIAL EKONOMI DENGAN PERSEPSI PETERNAK TERHADAP PENGEMBANGAN USAHA PETERNAKAN SAPI PERAH DI KOTA TOMOHON - Muhammad, Suryana D.S.; Legrans, R. A.J.; Lainawa, J. (Universitas Sam Ratulangi, 2014)
ABSTRACT RELATIONSHIP BEWEEN ECONOMICAL SOCIAL FACTOR AND HOUSEHOLD PERSEPTION ON DAIRY FARM DEVELOPMENT IN TOMOHON MUNICIPALITY. Dairy farm development was importantly connected with household farmer. Each household farmer had different economical social background. The objective of this study was to evaluate the relationship between economical social factor and household perception on dairy farm development in Tomohon municipality.This study was conducted at four districts in Tomohon municipality using thirty respondents of household farmers. Samples were determined by purposive sampling method involving three districts. Primer secunder data were used in this study. Results showed that household farmers at ages of 43 to 54 years old were 40 percents. The education period of the animal household was ranging from 12 to 16 years (46.7%). The experiemces as animal household of dairy cattle were ranging from 2 to 3 years. The frequency attending extension and skill training were ranging from 1 to 2 times (76.6 %), and 90 percents of animal household had income from Rp. 1,350,000 to Rp. 3,499,800 per month. Perseptions of animal household on dairy farm development in Tomohon municipality were generally good. Period of animal farm highly correlated Â with the perception household farmer in development of dairy farm in Tomohon municipality. Kata Kunci: Economical social factor, household farmer perception, dairy farm, Tomohon municipality.